2020
DOI: 10.1111/myc.13221
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the burden of tinea capitis among children in Africa

Abstract: Tinea capitis is a common and endemic dermatophytosis among school age children in Africa. However, the true burden of the disease is unknown in Africa. We aimed to estimate the burden of tinea capitis among children <18 years of age in Africa. A systematic review was performed using Embase, MEDLINE and the Cochrane Library of Systematic Reviews to identify articles on tinea capitis among children in Africa published between January 1990 and October 2020. The United Nation's Population data (2019) were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
3
31
0
2
Order By: Relevance
“…Tinea is a fungal infection caused by dermatophyte infestation, usually on the scalp, foot, hand, groin, nails, or face [ 20 ]. A recent study has indicated that one in five children in Africa has tinea capitis [ 21 ], and more than 96% (132.6 million) of cases occur in sub-Saharan Africa, mostly in Nigeria and Ethiopia [ 21 ]. The prevalence among schoolchildren in southern Ethiopia is about 25% [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tinea is a fungal infection caused by dermatophyte infestation, usually on the scalp, foot, hand, groin, nails, or face [ 20 ]. A recent study has indicated that one in five children in Africa has tinea capitis [ 21 ], and more than 96% (132.6 million) of cases occur in sub-Saharan Africa, mostly in Nigeria and Ethiopia [ 21 ]. The prevalence among schoolchildren in southern Ethiopia is about 25% [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a direct estimate based on the population of children below 15 years in Sierra Leone, we estimated the burden of fungal infections using a pooled prevalence of 19% reported in sub-Saharan Africa. 44 A total of 266,450 young persons in Sierra Leone have tinea capitis, giving a prevalence rate of 3,483 per 100,000 populations ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This trend is similar to estimates of tinea capitis in sub-Saharan Africa, where one in five children in sub-Saharan Africa have tinea capitis, making it one of the most common childhood diseases in the region. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Data from modelling suggests that of the ~530,000 AIDS deaths in Africa, over 250,000 are probably attributable to fungal diseases (3). High quality cancer and intensive care needs supportive diagnosis to prevent death from fungal infections.…”
Section: The Challenge Of Access To Refined Fungal Diagnosis: a New Step Forward For Low-and Middle-income Countriesmentioning
confidence: 99%
“…Tuberculosis(TB)-like fungal infections of the chest, notably chronic pulmonary aspergillosis and histoplasmosis, need addressing in TB programs in Africa. There is a huge problem of skin, hair and nails infection in African children, 135 million with tinea capitis as a quantified example (3). Fungal asthma in Africa can be addressed with antifungal therapy (4,5).…”
Section: The Challenge Of Access To Refined Fungal Diagnosis: a New Step Forward For Low-and Middle-income Countriesmentioning
confidence: 99%